1981
DOI: 10.1088/0022-3727/14/10/007
|View full text |Cite
|
Sign up to set email alerts
|

Tunnelling currents in Langmuir-Blodgett monolayers of stearic acid

Abstract: Tunnelling currents in stearic acid monolayers stored at 15°C in dry He have been monitored over an 8 week period. Measurements were made as a function of both temperature and also applied voltage. It is deduced that the observed currents are associated with defects which are gradually annealed out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…This behavior is not really sensitive to a particular molecular structure, since this type of bistability is observed in complex rotaxane-like molecules as well as in very simple alkane chains (CH 2 ) n assembled into LB films [38], and is not even exclusive to the organic films. The data strongly indicates that the switching has an extrinsic origin, and is related either to bistability of molecule-electrode orientation [22,23,34], or transport assisted by defects in the film [54,55].…”
Section: Molecular Switchesmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior is not really sensitive to a particular molecular structure, since this type of bistability is observed in complex rotaxane-like molecules as well as in very simple alkane chains (CH 2 ) n assembled into LB films [38], and is not even exclusive to the organic films. The data strongly indicates that the switching has an extrinsic origin, and is related either to bistability of molecule-electrode orientation [22,23,34], or transport assisted by defects in the film [54,55].…”
Section: Molecular Switchesmentioning
confidence: 99%
“…It was concluded some decades ago that the conduction through absorbed [54] and Langmuir-Blodgett [55] monolayers of fatty acids (CH 2 ) n , which we denote as Cn, is associated with defects. In particular, Polymeropoulos and Sagiv studied a variety of absorbed monolayers from C7 to C23 on Al/Al 2 O 3 substrates and found that the exponential dependence on the length of the molecular chains is only observed below the liquid nitrogen temperature of 77K, and no discernible length dependence was observed at higher temperatures [54].…”
Section: Extrinsic Switching In Organic Molecular Films: Role Of Defementioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of the electrical properties of LB films, such as conductance (Roberts, 1990) and capacitance (Srinivasan et al, 1988), are important because of the possible use of the films in electronic devices. It has been found, for example, that conductivity depends on the humidity of the ambient environment (Tredgold and Winter, 1981;Barraud et al, 19771, a result that is probably due to the presence of moisture in the films.…”
mentioning
confidence: 99%
“…In particular, Polymeropoulos and Sagiv have studied a variety of absorbed monolayers from C7 to C23 on Al/Al 2 O 3 substrates and found that the exponential dependence on the length of the molecular chains is only observed below the liquid nitrogen temperature of 77K, and no discernible length dependence was observed at higher temperatures [2]. The current varied strongly with the temperature for LB films on Al/Al 2 O 3 substrates in He atmosphere (believed to hinder the Al 2 O 3 growth) [3], which is not compatible with elastic tunneling. The 100-fold increase of resistance of the annealed films was attributed to the "annealing" of "defects" with time.…”
mentioning
confidence: 99%